Recent advances in regional treatment of breast carcinoma. (March 2016) - Bernier, Jacques; Rossier, Christine; Horiot, Jean-Claude
Abstract: Regional treatment is driven by surgery and radiotherapy in early breast cancer patients as sole or combined modalities. Lymph node dissection, performed in patients with positive sentinel lymph nodes accurately identifies malignant spread in the nodal areas and ensures high levels of control in the axilla. At the turn of the century, its real impact on survival indices was nevertheless questioned, also in terms of therapeutic index, by cooperative groups and meta-analyses. As regards radiotherapy, both the indication and extension of regional irradiation remained for a long time open questions, since these issues were never addressed by randomized trials. Recent results of controlled trials investigating the exact impact of nodal surgery or irradiation on survival indices provide useful tools to optimize the regional treatment in patients with early breast cancer. Caution on interpreting some of the key messages from these controlled studies is nevertheless mandatory due to methodological limitations and caveats identified in several of these major trials enrolling patients with positive sentinel nodes.